Secretory carrier-associated membrane protein 5 regulates cell-surface targeting of T-type calcium channels - Emilio R. Mustafá; Konstantin Weiß; Norbert Weiss (Taylor & Francis Group, 2023)
ABSTRACTMissense mutations in the human secretary carrier-associated membrane protein 5 (SCAMP5) cause a variety of neurological disorders including neurodevelopmental delay, epilepsy, and Parkinson's disease. We recently documented the importance of SCAMP2 in the regulation of T-type calcium channel expression in the plasma membrane. Here, we show that similar to SCAMP2, the co-expression of SCAMP5 in tsA-201 cells expressing recombinant Cav3.1, Cav3.2, and Cav3.3 channels nearly abolished whole-cell T-type currents. Recording of intramembrane charge movements revealed that SCAMP5-induced inhibition of T-type currents is primarily caused by the reduced expression of functional channels in the plasma membrane. Moreover, we show that SCAMP5-mediated downregulation of Cav3.2 channels is essentially preserved with disease-causing SCAMP5 R91W and G180W mutations. Hence, this study extends our previous findings with SCAMP2 and indicates that SCAMP5 also contributes to repressing the expression of T-type channels in the plasma membrane.